U.S. Dental School Applicants and Enrollees, 2014 Entering Class. Issue 11 (1st November 2015) - Wanchek, Tanya; Cook, Bryan J.; Anderson, Eugene L.; Duranleau, Lauren; Booker, Carolyn
Abstract : This report analyzes data collected annually by the American Dental Education Association (ADEA) on the characteristics of applicants to and first‐year enrollees in dental schools. Among the key findings this year are that, since 2010, there has been a gradual decline in the number of individuals taking the Dental Admission Test (DAT), while the number applying to dental schools has remained relatively flat. During the same five‐year time period, the number of first‐year dental students has continuously increased. The result is an increasing rate of enrollment among applicants. While the overwhelming majority of dental schools utilize some aspect of a holistic admissions process, the DAT scores and grade point averages of applicants and enrollees continue to rise. Unlike a decade ago, women now account for nearly half of all applicants and enrollees. At least part of the gain has come from a decline in the number of men applicants, rather than a change in the enrollment rate. Among underrepresented minorities, there remains a relatively low number of applicants and a lower than average enrollment rate. Overall, by analyzing data about individuals applying to and matriculating in dental schools, this report provides a window into the future dental workforce.